DEMNITATEA UMANĂ, LIBERTATEA VOINȚEI ȘI PROCESUL CONȘTIINȚEI ÎN REPERE DIN SCRIERI PATRISTICE DINTRE SECOLELE AL II-LEA ȘI AL V-LEA (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Dignity, Freedom of Will and the Conscience Process Anchored in Church Fathers’ Writings From Second to the Fifth CenturyIn the tradition of the Church Fathers human dignity, moral freedom and a functional conscience remained stable anchors that created a context into which a practical understanding of salvation for the human being. The following article summarizes, reinterprets and opens further perspectives that build on the Kendall Soulen’s and Linda Woodheads’ research published in introductory chapter of God and Human Dignity, attempting to open outlooks for future research.